Efektivitas Karbon Aktif Sekam Padi dalam Menurunkan Mangan (Mn) Air Sumur Gali di Desa Amplas Kecamtan Percut Sei Tuan Kabupate Deli Serdang - ika surya agustiani; taufik ashar; nurmaini * (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT Water is an second essential element for life after oxygen. The clean water must have chemical, physical, and biological quality. One of the chemical parameters is Manganese (Mn).The people in Desa Amplas, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang use dug well water that contains high concentration of manganese (Mn), so that the process to decrease it is necessarily needed. Activated carbon of rice husk is one of the alternative materials that are used to decrease the concentration of manganese in the water. The purpose of this research was to determine effectiveness of activated carbon of rice husk in decreasing Mn concentration in the dug well water in Desa Amplas. The type of research was Quasy Experiment with Pre and Post test design. The sample was dug well water mixed 1 gr, 2 gr, and 3 gr of the activated carbon of rice husk into every 100 mL water and another one was not given at all (0 gr) this one was as control. Each done 4 times. The research found that the concentration of Mn in water sample without being mixed the activated carbon (control) is 3,35579 mg/L, in 1 gr is 2,97591 mg/L, in 2 gr is 2,47997mg/L, and in 3 gr is 1,68893 mg/L while according to Permenkes RI No.416 tahun 1990, Mn is 0,5 mg/L. Based on Kruskal-wallis test at level of confidence of 95%. result shows the significant (p = 0,003) difference between various treatment of the activated carbon of rice husk to decrease Mn concentration dug well water in Amplas village. BNT test result shows that activated carbon of rice husk that is able to decrease the biggest concentration of Mn is in 3 gr. The usage of activated carbon of rice husk is effective to decrease Mn concentration but fulfilling standard quality Permenkes RI No. 416 of 1990 not yet that exceed 0,5 mg/L. Suggested to the people in Desa Amplas, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang not only using the activated carbon of rice husk in dug well water treatment but also accompanied with other chemicals such as Zeolite. Keyword : Use the Activated Carbon of Rice Husk, Mn Concentration, Dug Well Water.